Utilization of stretch-shortening cycles in cross-country skiing - Norman, R.; Linnamo, V.; Komi, P. V. (Neuromuscular aspects of sport performance, 2011)
This chapter contains sections titled: Introduction, SSCs reviewed, Evidence of use of SSC in cross-country skiing, Summary and discussion, References.